Activities of occupational nurses working in companies - Daniela Inês Thier Roloff; Marta Regina Cezar-Vaz; Clarice Alves Bonow; Marlise Capa Verde Almeida de Mello (Rev Rene)
Objective: to understand the activities of occupational nurses working in companies.Methods: qualitative study, with eight occupational nurses working in seven companies. Data collected through interviews and non-participant observations analyzed by the Content Analysis method. Results: nurses perform activities of assistance, administrative, educational and integrative research, where the purpose of these traverses the approach to the worker and is interfered by the characteristics of the occupational health service and the institutional context. Conclusion: the work of nurses is influenced by the size of the health and safety team and the socioeconomic characteristics of companies and municipalities, shaping the labor market and posing a challenge for these professionals.